2014
DOI: 10.1007/s15010-014-0655-8
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Listeria monocytogenes infection in a 2-year-old immunocompetent child

Abstract: Central nervous system infection and sepsis are the most frequently observed clinical presentations of listeriosis infection; however, they are rare in immunocompetent children beyond the neonatal period. In the presented case, we described gastrointestinal involvement, subacute meningitis, sinusitis and sepsis in a two-year-old previously healthy child with acute infection caused by Listeria monocytogenes. We suggest that the infection was probably enhanced by an inappropriate corticosteroid treatment at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Like other causes of bacteremia, listeriosis can cause fulminant disease, presenting with severe systemic illness leading to distributive shock and multiorgan failure, usually in the immunocompromised. Although there are several case reports of Listeria meningoencephalitis in immunocompetent hosts, the presence of sepsis secondary to Listeria in otherwise healthy individuals, as in our patient, is extremely uncommon . Only the two patients reported by Von Rotz et al.…”
Section: Discussionmentioning
confidence: 49%
“…Like other causes of bacteremia, listeriosis can cause fulminant disease, presenting with severe systemic illness leading to distributive shock and multiorgan failure, usually in the immunocompromised. Although there are several case reports of Listeria meningoencephalitis in immunocompetent hosts, the presence of sepsis secondary to Listeria in otherwise healthy individuals, as in our patient, is extremely uncommon . Only the two patients reported by Von Rotz et al.…”
Section: Discussionmentioning
confidence: 49%
“…In this study, the peripheral blood leukocytes of 3 patients (Patient 2, 7, 8) were close to normal yet the levels of neutrophils and CRP were increased in all cases. Previous reports showed that typical monocyte predominance was different from other general forms of meningitis (12,13), whereas neutrophilic predominance has been reported in other studies (10,11,(14)(15)(16). These findings may be due to the increases in monocytes due to the presence of L. monocytogenes which is a facultative intracellular pathogen.…”
Section: Discussionmentioning
confidence: 70%
“…Despite most non-perinatal listeriosis cases are people with comorbid conditions, the study also indicated that neurological listeriosis can affect people without (known) underlying diseases and very young immunocompetent children. Other recent case reports also revealed that listeriosis can affect very young children and that an appropriate treatment at the onset, based on intravenous ampicillin in the first line therapy, can avoid the spread of the infection in the patient [ 10 13 ].…”
Section: Discussionmentioning
confidence: 99%